An IoT-based ambient assisted living for elderly care and monitoring in COVID-19 pandemic using arti cial intelligence and deep learning - Bhowmick, Shovon; Ferdous, Tarik; Momtaz, Raihan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.